2014
DOI: 10.1007/s10900-014-9958-z
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Food Environment and its Effects on Obesity in the United States: A Systematic Review of Methods and Results

Abstract: We identified fifty-one peer-reviewed studies that geospatially analyzed the relationship between the community nutrition environment (CNE) and obesity. Eighty percent of studies found at least one significant association between the CNE and obesity. However we calculated the proportion of studies that found at least one significant association between the CNE and obesity in the expected direction for each food store type and measurement technique, and the proportion across the different store types and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 43 publications
3
122
0
2
Order By: Relevance
“…Effective policies to combat unhealthy diets go beyond the individual and need to take a population perspective (Franco et al, 2016;Eisenhauer, 2001). Cross-cultural comparison studies, which use standardized and reliable methods are needed in order to understand the relationship between the food environment and diet-related health outcomes (Ball et al, 2015;Gamba et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective policies to combat unhealthy diets go beyond the individual and need to take a population perspective (Franco et al, 2016;Eisenhauer, 2001). Cross-cultural comparison studies, which use standardized and reliable methods are needed in order to understand the relationship between the food environment and diet-related health outcomes (Ball et al, 2015;Gamba et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-national studies are thus warranted considering the large international differences in the patterning of the retail food environment (Flavian et al, 2002;Thornton et al, 2013). Systematic reviews focusing on the effect of local food environments on dietary behaviors have shown consistent evidence for existing inequalities regarding food access in the US, but also highlighted several limitations (Black et al, 2014;Cobb et al, 2015;Feng et al, 2010;Gamba et al, 2015;Holsten, 2009). The comparability of previous studies may be limited for several methodological and theoretical reasons:…”
Section: Introductionmentioning
confidence: 99%
“…A lack of robust evidence for a causal link or association does not mean that a particular topic is not important; researchers may not have developed sufficient methods to investigate suspected links. For example, there is contradictory evidence about the association between food access and obesity in high income countries such as the USA and Canada (Gamba et al 2014, Cobb et al 2015); yet researchers point more to the methodological limitations of the studies than the expectation that food access may be unimportant (Penney et al 2015). There is also a much more widely developed evidence base in high income countries (HICs), compared to LMICs, potentially obscuring the importance of particular environmental health issues in those countries (Prasad et al 2016).…”
Section: Combining Indicators and Categoriesmentioning
confidence: 99%
“…Creating initiatives to understand and mitigate obesity has been considered one of the major challenges of the 21st century and childhood obesity prevention has become a global priority (3) . Several studies have demonstrated that both dietary behaviours and the development of obesity and chronic diseases are related to a range of complex social and environmental influences that extend beyond the notion of individual choices (4)(5)(6)(7)(8)(9)(10)(11) . The food environment can refer to macro-or community-level environments, such as the type, density, location and proximity to food outlets (e.g.…”
mentioning
confidence: 99%